SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA KARYAWAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA CV. GRAHA MESIN GLOBALINDO MALANG - Rendy Okta Maulana; Mochamad Husni; Jauharul Maknunah (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2025)
Graha Mesin Globlindo Malang has been assessing employee performance conventional and is a direction that tends to subjectively, the assessment manager to an employee who becomes the object of assessment. From this, it needs a system that aims to help the management of CV. Graha Mesin Globlindo Malang to assess the employee's performance for the next decision could be made in accordance with the standard of the work, the target or targets that have been determined in advance and agreed upon. Methods of decision support used in this study is the Simple Additive Weighting (SAW) is a method that is based on the sum of the value of the matrix normalized (R) with a value weighted on the assessment criteria achievement of the work, sanctions, years of delay time off work, absenteeism working with preferesi value to then be obtained ranking is based on the value of preferences (Vi). The result showed that with the establishment of a decision support system can evaluate the employee's performance appraisal employee performance in the marketing division and information technology (IT) objectively and do not require a longer time than the previous method of evaluation.